Insulin, but Not Metformin, Supports Wound Healing Process in Rats with Streptozotocin-Induced Diabetes - Mieczkowski M (Dove Medical Press, 2021)
Mateusz Mieczkowski,1 Beata Mrozikiewicz-Rakowska,1 Tomasz Siwko,1 Magdalena Bujalska-Zadrozny,2 Anna de Corde-Skurska,2 Renata Wolinska,2 Emilia Gasinska,2 Tomasz Grzela,3 Piotr Foltynski,4 Michal Kowara,5 Zofia Mieczkowska,1 Leszek Czupryniak1 1Department of Diabetology and Internal Medicine, Medical University of Warsaw, Warsaw, Poland; 2Department of Pharmacodynamics, Medical University of Warsaw, Warsaw, Poland; 3Department of Histology and Embryology, Medical University of Warsaw, Warsaw, Poland; 4Nalecz Institute of Biocybernetics and Biomedical Engineering Polish Academy of Sciences, Warsaw, Poland; 5Department of Cardiology, Medical University of Warsaw, Warsaw, PolandCorrespondence: Beata Mrozikiewicz-RakowskaDepartment of Diabetology and Internal Medicine, Medical University of Warsaw, Poland ul. Banacha 1A, Warsaw, 02-097, PolandTel +48 600 311 399Fax +48225992832Email rakowskab123@gmail.comPurpose: Optimal glycemic control is crucial for proper wound healing in patients with diabetes. However, it is not clear whether other antidiabetic drugs support wound healing in mechanisms different from the normalization of blood glucose control. We assessed the effect of insulin and metformin administration on the wound healing process in rats with streptozotocin-induced diabetes.Methods: The study was conducted on 200 male Wistar rats with streptozotocin-induced diabetes. In the last phase of the study, 45 rats, with the most stable glucose levels in the range of 350– 500 mg/dL, were divided into three groups: group I received human non-protamine insulin subcutaneously (5 IU/kg body mass) once a day, group II received metformin intragastrically (500 mg/kg b.m.), and group III (control) was given saline subcutaneously. After 14 days of antidiabetic treatment, a 2 cm × 2 cm thin layer of skin was cut from each rat’s dorsum and a 4 cm disk with a hole in its center was sewn in to stabilize the skin and standardize the healing process. The wound healing process was followed up for 9 days, with assessment every 3 days. Biopsy samples were subjected to hematoxylin and eosin staining and immunohistochemical assays.Results: Analysis of variance revealed significant influence of treatment type (insulin, control, or metformin) on the relative change in wound surface area. The wound healing process in rats treated with insulin was more effective than in the metformin and control groups. Wound tissue samples taken from the insulin-treated animals presented significantly lower levels of inflammatory infiltration. Immunohistochemical assessment showed the greatest density of centers of proliferation Ki-67 in insulin-treated animals.Conclusion: These results suggest that an insulin-based treatment is more beneficial than metformin, in terms of accelerating the wound healing process in an animal model of streptozocin-induced diabetes.Keywords: diabetes mellitus, neuropathy, ulceration, animal model